Cellular immunity and acute hepatitis C infection. - Fitzmaurice, K; Klenerman, P (2008)
Hepatitis C virus (HCV) infects an estimated 170 million people globally and persistent infection within the liver is the usual outcome of infection. The resulting liver disease leads to substantial morbidity and to date no vaccine exists. Furthermore the treatments available are frequently ineffective. A minority of those exposed will however successfully control the virus and the factors that dictate this remain elusive. The events that occur in the immediate and early phase post exposure are thought to play a crucial role in determining the outcome and virus specific T cells have a confirmed role in directing the immune response towards a successful outcome. An understanding of the T cell responses and the strategies, which allow the virus to evade these responses in the majority, is an essential prerequisite both for vaccine design and the development of therapeutic agents. We review here the characteristics of the cellular immune responses in acute infection and how the virus manages to undermine these responses and establish chronicity.